Homocysteine and female fertility, pregnancy loss and offspring birthweight: a two-sample Mendelian randomization study - Kjaergaard, Alisa D.; Wu, Yanxin; Ming, Wai-Kit; Wang, Zillian; Kjaergaard, Mathias N.; Ellervik, Christina (European journal of clinical nutrition, 2022)
Background/Objectives Observational studies link elevated homocysteine concentrations (Hcy) with female fertility, pregnancy loss, and low offspring birthweight. Maternal rs1801133, a functional variant in MTHFR strongly associated with lifelong elevated Hcy, is associated with recurrent pregnancy loss and offspring birthweight in Asian women. We investigated if genetically elevated Hcy is associated with fertility, pregnancy loss, and offspring birthweight in European women. Subjects/Methods We performed a two-sample Mendelian randomization (MR) study using publicly available data. We obtained 18 genetic variants (five involved in Hcy metabolism) explaining up to 5.9% of the variance in Hcy from a genome-wide association meta-analysis of 44,147 European individuals (82% women). We investigated fertility (including age at menopause), pregnancy loss, and offspring birthweight in the UK Biobank ( N = 194,174), EGG ( N = 190,406), and ReproGen ( N = 69,360–252,514) consortia using summary statistics. We calculated inverse-variance weighted, and several sensitivity MR regression statistics. Results rs1801133 was associated with a 7.45 months (95% CI: 4.09, 10.80) increase in age at menopause and 29.69 (12.87, 46.51) g decrease in offspring birthweight per SD increase in Hcy in the UK biobank, and confirmed in EGG and ReproGen. MR for Hcy metabolism alone (five variants in MTHFR, MTR, CBS ) showed similar results for offspring birthweight across consortia. However, using all 18 variants resulted in no association for any of the outcomes across consortia. Conclusion Hcy and suggestively vitamin B variants are most likely the drug targets for folate supplementation in pregnant women on the offspring birthweight, while Hcy variants related to renal function or diabetes are not involved.